RUSSIAN SYNTAX IN THE MIRROR OF CORPUS LINGUISTICS: NEW DATA ON NORM AND USAGE AS A RESOURCE FOR MODERN LINGUODIDACTICS (Web of Teachers: Inderscience Research, 2026)
The article is devoted to the application of corpus linguistics data — primarily the Russian National Corpus (RNC) — in teaching syntax at secondary and higher school levels. The gap between normative grammatical descriptions recorded in textbooks and the actual syntactic usage captured by corpus data is analyzed: the functioning of parcellation, ellipsis, non-standard word orders, and colloquial syntactic constructions across texts of various styles and genres. The necessity of transitioning from a normative-prescriptive to a corpus-descriptive model of syntax teaching is substantiated — one that does not abolish the normative aspect but significantly enriches students' understanding of real language functioning. A system of lessons built on working with corpus data is proposed, ranging from simple RNC searches to independent mini-research of syntactic phenomena. The experience of implementing the corpus approach in classes on contemporary Russian language at Karshi State University is described.